Nature-based Tourism in Maine: The State’s Role in Promoting a Strong Tourism Industry - Munding, Elizabeth; Daigle, John (Maine Policy Review, 2007)
Tourism is Maine’s largest industry and, perhaps also, one of the least well understood and appreciated by the state’s citizens. Conventional wisdom suggests that tourism yields unwanted crowds and low-paying jobs. Yet closer analysis suggests that tourism does and has a yet-to-be-realized potential to enhance the well-being and sustainability of communities, particularly through high-quality, nature-based experiences that leverage Maine’s extraordinary landscapes, wilderness, and rural culture. Elizabeth Munding and John Daigle summarize what was learned as a result of Munding’s interviews with close to 50 tourism stakeholders throughout Maine. Although this study covered four major aspects of Maine’s tourism industry, here the authors focus on the state’s role and responsibilities in strengthening, promoting, and sustaining a nature-based tourism industry in Maine.
Keywords: Maine tourism; nature tourism; eco-tourism